BIOSORPSI Hg(II) DENGAN KULIT BUAH KAKAO (Theobroma cacao L.) - Fitri Fitri; Syaiful Bahri; Nurakhirawati Nurakhirawati (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
ABSTRACT This study aims are determine the amount of biosorbent from cocoa fruit skin and required best interaction time to be able to adsorb Hg(II) in solution. This study was conducted using a completely randomized design (CRD) with 5 variations of biosorbent amount is 2, 4, 6, 8, and 10 grams and contact time is 30, 60, 90, 120, 150 minutes. Each treatment was repeated twice. The results showed that the best amount of biosorbent in the adsorption of Hg(II) is 99.11% with biosorbent weight 2 grams. Best contact time for the adsorption of Hg(II) is 90 minutes with the amount of adsorbed as much as 99.82%. Keywords : Biosorption, Cocoa fruit skin, Mercury